Evaluation of Ocular Surface and Meibomian Glands Alterations with Meibography in Patients with Inactive Behçet's Uveitis. (3rd April 2019) - Karaca, Irmak; Palamar, Melis; Guven Yilmaz, Suzan; Ates, Halil
ABSTRACT: Purpose : To evaluate the ocular surface and meibography of patients with inactive Behçet's uveitis. Methods : Twenty-five right eyes of 25 patients with inactive Behçet's uveitis (Group 1) and 25 right eyes of 25 healthy individuals (Group 2) were enrolled. Detailed eye examination along with Schirmer 1 test, tear film break-up time (t-BUT), ocular surface staining with fluorescein and Oxford scoring, and ocular surface disease index (OSDI) score assessment were performed. Lower and upper eyelid Meibomian glands were examined with infrared filter of slit-lamp biomicroscope (SL-D701 with DC-4 digital camera and BG-5 background illuminator, TOPCON, Tokyo, Japan (from grade 0 (no dropout of Meibomian glands) to grade 3 (gland dropout >2/3 of the total Meibomian glands)). Results : The mean ages were 36.84 ± 7.39 (range, 23–59) and 33.88 ± 8.25 (range, 18–55) in Group 1 and Group 2, respectively ( p = 0.547). When compared with Group 2, in Group 1, best-corrected visual acuity (0.28 vs. 0.00 logMAR, p < 0.001), Schirmer 1 test (18.68 vs. 23.69, p = 0.017) and mean tear film break-up time (10.76 vs. 13.36, p = 0.026) were significantly lower; Oxford scale and OSDI scores were higher ( p = 0.039 and p < 0.001, respectively). No significant difference in lower, upper and total (upper + lower) meiboscores were detected in between groups ( p = 0.062, p = 0.228 and p = 0.152, respectively). Conclusion : Despite the tendency toward dry eye syndrome, Behçet's uveitis does not seem to be associated with quantitative Meibomian gland changes, which is demonstrated by gland drop-out with meibography.